Perbedaan Pemberian Asam Valproat dan Fenobarbital terhadap Kadar Kalsium Darah Pasien Epilepsi Anak di RSUD Dr. Moewardi - Friska Kusumaningtyas; Fadhilah Tia Nur; Dyah Ratna Budiani (Nexus Kedokteran Klinik, 2013)
Background : Antiepileptic drugs have different mechanisms. Meanwhile valproate acid and phenobarbital have similar mechanism, inactivation of voltage gated Ca2+ channels, Na+ channels, and increased activity of GABAergic inhibitory. However, the mechanism of phenobarbital also induces cytochrome P450 (CYP450) enzymes that affect the metabolism of vitamin D. The aim of this study was to examine the differences between valproic acid and phenobarbital on blood calcium levels of pediatric epilepsy. Methods : The cross sectional study was conducted by 24 pediatric epilepsy in the pediatric neurology clinic of RSUD Dr. Moewardi who met the inclusion criteria. Calcium ion levels in blood serum obtained from the medical records of pediatric patients who had been done routine laboratory tests about the side effects of antiepileptic drugs. Data normality was tested by Shapiro-Wilk. The differences of giving valproic acid and phenobarbital on calcium ion level of blood serum were analyzed by the Mann-Whitney test. The correlation between long term drug use and calcium ion levels in blood serum were analyzed by Spearman test. Results : The analysis results show that there is no difference between calcium ion levels in blood serum of valproic acid and phenobarbital of pediatric epilepsy in RSUD Dr. Moewardi with p = 0.881 (p > 0.05). Correlation analyze show that there is no correlation between duration of drug intake and calcium ion levels in blood serum levels with p = 0.191 (p > 0.05), 35.7% of subjects had a negative correlation for valproic acid and p = 0.548 (p > 0.05), 23.2% of subjects had a negative correlation for phenobarbital. Conclusion : There is no significant difference between calcium ion levels in blood serum of valproic acid and phenobarbital in pediatric epilepsy in RSUD Dr. Moewardi. As well as, there is a weak correlation between duration of drug intake and calcium ion in blood serum. Keywords : epilepsy, antiepileptic drug, valproic acid, phenobarbital, calcium ion